2014
DOI: 10.1093/ecco-jcc/jju021
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Inflammatory Bowel Disease Treatment Recommendations Based on Appropriateness Ratings: do Practicing Gastroenterologists Agree with Experts?

Abstract: In about one-third of vignette cases, inflammatory bowel disease treatment propositions made by practicing gastroenterologists diverged from expert recommendations. Practicing gastroenterologists may experience difficulty in applying recommendations in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…62 Evidence-based clinical pathways are one strategy for standardizing care, improving appropriateness, and reducing variability in care, and thereby improve outcomes and reduce costs; but they are often complex, out of date, lack credibility, or poorly implemented. 63,64 Suboptimal adherence to international, evidence-based guidelines is an ongoing problem across various aspects of IBD care. [65][66][67] Clinician engagement, staying up-to-date with the research, and strategies to improve uptake are imperative if clinical pathways and guidelines are to improve the appropriateness of IBD care delivery.…”
Section: Variability In Care and Standardizing Care To Facilitate App...mentioning
confidence: 99%
“…62 Evidence-based clinical pathways are one strategy for standardizing care, improving appropriateness, and reducing variability in care, and thereby improve outcomes and reduce costs; but they are often complex, out of date, lack credibility, or poorly implemented. 63,64 Suboptimal adherence to international, evidence-based guidelines is an ongoing problem across various aspects of IBD care. [65][66][67] Clinician engagement, staying up-to-date with the research, and strategies to improve uptake are imperative if clinical pathways and guidelines are to improve the appropriateness of IBD care delivery.…”
Section: Variability In Care and Standardizing Care To Facilitate App...mentioning
confidence: 99%
“…The treatment decisions made by IBD care providers in daily practice are often different from those recommended by experts or supported by latest research outcomes. In addition, gastroenterologists may experience difficulty in assessing disease activity or severity as recommended by guidelines, and in applying treatment recommendations, in daily practice [69]. A survey conducted with community gastroenterologists and UC experts in the United States identified that, when it came to areas of uncertainty in UC treatment, dramatic variations in approach existed between the 2 groups [70].…”
Section: Patient-focused Unmet Needsmentioning
confidence: 99%
“…So fanden z. B. Pittet et al [10] heraus, dass ca. 1/3 der praktizierenden Ärzte/innen in ihren Behandlungsempfehlungen von den Leitlinien, die von einem Exper tengremium derselben Disziplin erstellt wurden, abwichen.…”
Section: Diskussionunclassified